2023
DOI: 10.1029/2023jg007525
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Drivers of Coastal Treeline Elevation

G. D. Molino,
J. A. Carr,
N. K. Ganju
et al.

Abstract: Sea level rise is leading to the rapid migration of marshes into coastal forests and other terrestrial ecosystems. Although complex biophysical interactions likely govern these ecosystem transitions, projections of sea level driven land conversion commonly rely on a simplified “threshold elevation” that represents the elevation of the marsh‐upland boundary based on tidal datums alone. To determine the influence of biophysical drivers on threshold elevations, and their implication for land conversion, we examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 91 publications
(193 reference statements)
1
0
0
Order By: Relevance
“…The results of this investigation also suggest that the one-to-one replacement of habitat or ecogeomorphologic cross-shore profile translation [31,33] is unlikely under conditions of 21st century accelerating sea level rise within the study domain, as has recently been reported in the Delaware and Chesapeake Bay regions [54]. The data assembled during this investigation-albeit limited-suggest that the transition will not simply progress inland over time as a well-defined ecotone (see also [33,54,55]). This can be demonstrated through an inspection of the paired rates of marsh migration and forest retreat measured in the studies conducted in Delaware Bay and Northwest Florida (Table 1).…”
Section: Discussionsupporting
confidence: 53%
“…The results of this investigation also suggest that the one-to-one replacement of habitat or ecogeomorphologic cross-shore profile translation [31,33] is unlikely under conditions of 21st century accelerating sea level rise within the study domain, as has recently been reported in the Delaware and Chesapeake Bay regions [54]. The data assembled during this investigation-albeit limited-suggest that the transition will not simply progress inland over time as a well-defined ecotone (see also [33,54,55]). This can be demonstrated through an inspection of the paired rates of marsh migration and forest retreat measured in the studies conducted in Delaware Bay and Northwest Florida (Table 1).…”
Section: Discussionsupporting
confidence: 53%